Використання інноваційних групових методів при вивченні англійської мови у ЗВО - Пащенко, Юлія Петрівна; Пащенко, Юлия Петровна; Paschenko, Yuliia; Колесніков, Максим Олександрович; Колесников, Максим Александрович; Kolesnikov, Maksym (ТДАТУ імені Дмитра Моторного, 2020)
UK: У статті приведена характеристика використання інноваційних групових методів у навчанні англійської мови здобувачів вищої освіти, проведено дослідження розробки групових методів в сучасній науці, проаналізовано особливості підготовки майбутніх викладачів англійської мови до професійної діяльності. EN: The article describes the characteristics of the use of innovative group methods of teaching English to higher education students. The analysis of group methods development in modern science was carried out. It was shown the peculiarities and modern condition of professional training of future teachers to work. The study is aimed at testing the effectiveness of group methods of teaching English.
The Use of Innovative Group Methods of Teaching English in Higher Educational Establishments
Keywords: групові методи; здобувачі вищої освіти; навчання англійської мови; group methods; students of Higher Educational Establishments; teaching English language